2017
DOI: 10.1016/j.ijsu.2017.07.107
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gum chewing on ameliorating ileus following colorectal surgery: A meta-analysis of 18 randomized controlled trials

Abstract: Based on current evidence, chewing gum offers an inexpensive, well-tolerated, safe and effective method to ameliorate ileus following colorectal surgery. However, tightly controlled, randomized and considerably larger multicenter trials are warranted to further validate our findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 35 publications
2
43
0
1
Order By: Relevance
“…[15] In the previous studies using chewing gum as a sham feeding, the case series of major abdominal surgery and colorectal resection have generally been employed. [13] It is clearly stated in the literature that these interventions are the most important factors of POI. [20] We think that studies conducted with the main factors in this multifactorial clinical condition will not provide healthy data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[15] In the previous studies using chewing gum as a sham feeding, the case series of major abdominal surgery and colorectal resection have generally been employed. [13] It is clearly stated in the literature that these interventions are the most important factors of POI. [20] We think that studies conducted with the main factors in this multifactorial clinical condition will not provide healthy data.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple meta-analyses and reviews have published the positive effects of chewing gum on the intestinal motility as a sham feeding after abdominal surgery. [12][13] After recognizing the clinical benefits of chewing gum, it has been suggested that it will have a positive effect on the intestinal motility in two different pathways with the combination of nicotine. The first pathway has been hypothesized as the stimulation of cephalo-vagal reflex by chewing gum and the second pathway as the activation of cholinergic anti-inflammatory pathway by nicotine.…”
Section: Introductionmentioning
confidence: 99%
“…Coffee has been shown to reduce time to first bowel movement after colorectal and gynecologic surgery by 9.4–15.4 h on average [ 17 , 23 , 24 ]. A recent meta-analysis on the effect of chewing gum on postoperative ileus after colorectal surgery, including 1736 patients from 18 RCTs, observed a reduction of 16.4 h (95% confidence interval: − 22.7; − 10.2) of time to first bowel movement [ 25 ]. One of the two studies in small bowel capsule endoscopy found a significant reduction of transit time.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that chewing gum may stimulate bowel motility -via vagal stimulation or gastrointestinal hormones secretion -with an earlier return of intestinal function and reduced LOS [100] , but unfortunately the vast majority of colorectal studies are small sized and of poor quality [101,102] . A large RCT on 402 patients clearly demonstrated that, although there is no detriment, there is no beneficial effect either [103] .…”
Section: Prevention Of Postoperative Ileusmentioning
confidence: 99%